Rancang Bangun Prototipe Solar Home System Menggunakan Baterai Lithium Sebagai Penyimpan Energi - Marhatang, Marhatang; Yusuf Yunus, Muhammad; Sonong, Sonong; Lewi, Lewi; Tandioga, Remigius; Ruswandi Djalal, Muhammad (Jurnal JEETech, 2024)
Utilizing the Solar Home System requires a battery as an energy storage medium produced from photovoltaic modules. Today's batteries are lead-carbon Valve Regulated Lead Acid (VRLA) batteries. This type of battery has a 90-95% round-trip efficiency and a deep discharge (DOD) level of 80%. This type of battery is not environmentally friendly because it produces lead acid. Therefore, the development of batteries in the SHS system from lithium battery technology is carried out. Besides being environmentally friendly, its round-trip efficiency is quite good compared to lead-carbon, which is 92-96% with a DOD level of 100%. In this study, it is proposed to apply lithium batteries on a lab scale so that they can assist students in developing scientific fields, especially lithium battery-based energy storage. In addition, this research will describe the process of making and prototyping lithium batteries in solar practicum learning media. From the test results obtained, a laboratory-scale Solar Home System prototype for solar power system practicum using Lithium batteries as Energy Storage. The average effect of charging the battery is 21.09 watts. With the highest battery charging voltage set at 14.08 Vdc. And the highest charging current rate is 1.37 A, with the highest battery charging efficiency rate of 12%. The characteristics of the Lithium battery itself, the DoD shown is also good when the capacity read on the battery meter is 0%. The battery can still supply 15 watts of load for 20 minutes